Synergetic learning structure-based neuro-optimal fault tolerant control for unknown nonlinear systems. (November 2022) - Xia, Hongbing; Zhao, Bo; Guo, Ping
Abstract: In this paper, a synergetic learning structure-based neuro-optimal fault tolerant control (SLSNOFTC) method is proposed for unknown nonlinear continuous-time systems with actuator failures. Under the framework of the synergetic learning structure (SLS), the optimal control input and the actuator failure are viewed as two subsystems. Then, the fault tolerant control (FTC) problem can be regarded as a two-player zero-sum differential game according to the game theory. A radial basis function neural network-based identifier, which uses the measured input/output data, is constructed to identify the completely unknown system dynamics. To develop the SLSNOFTC method, the Hamilton–Jacobi–Isaacs equation is solved by an asymptotically stable critic neural network (ASCNN) which is composed of cooperative adaptive tuning laws. Besides, with the help of the Lyapunov stability analysis, the identification error, the weight error of ASCNN, and all signals of closed-loop system are guaranteed to be converged to zero asymptotically, rather than uniformly ultimately bounded. Numerical simulation examples further verify the effectiveness and reliability of the proposed method.